A Case Study On TESCO Corporation : RFID - Ahmed, Mohammed Shafiq (2005)
The purpose of this final thesis is to develop a model for justification and evaluation of RFID technology. Tesco planned to have RFID technology in operation throughout its supply chain. The project finally resulted in an approach pattern for consideration and evaluation of RFID technology.